Physical and chemical characteristics of oil palm plantation soil: a new lead in forensic investigation - Rus Dina Rus Din; Seri Mirianti Ishar; Hemananthini Naganathan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Soil sample is one of the important evidence that can be found in crime scene. Unknown soil sample can be analysed and compared with reference sample in order to determine the origin as its physical and chemical components possess unique characteristics. The purpose of this study is to determine the physical and chemical characteristics of soil from oil palm plantations in Perak, Malaysia to assist forensic investigation. Total of 97 topsoil samples were collected from three different oil palm plantations in Perak. Particle size distribution was obtained using dry sieving technique and colour of soil sample was examined under three conditions that are dry, moist and ashed. Soil pH was measured using pH meter and percentage of composition of soil organic matter (SOM) was determined by weighing the sample before and after ignition. Result showed that the composition of particle size <0.18mm was within the range of 5.57-21.11% whereas for particle size between 0.18mm - 0.6mm was within 31.62 - 52.96% and 25.78-66.86% for particle size >0.6mm. The color mode of soil after oven dried, moistened and ashed was greyish brown (10YR 5/2), very dark greyish brown (10YR 3/2) and light yellowish brown (10YR 6/4) respectively. Soil pH was in the range of 5.79 – 6.70. The percentage of SOM was between 3.29 - 20.48%. The physical and chemical characteristics of soil analysed in this study from three different locations of oil palm plantations varied and it is possible to discriminate these locations based on the analysis highlighted in this study.